2017
DOI: 10.1016/j.shaw.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Trans, Trans -Muconic Acid is Not a Reliable Biomarker for Low-level Environmental and Occupational Benzene Exposures

Abstract: BackgroundBenzene is a known occupational and environmental pollutant. Its urinary metabolite trans, trans-muconic acid (tt-MA) has been introduced by some environmental and occupational health regulatory associations as a biological index for the assessment of benzene exposure; however, recently, doubts have been raised about the specificity of tt-MA for low-level benzene exposures. In the present study, we investigated the association between urinary levels of tt-MA and inhalational exposure to benzene in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 27 publications
2
25
0
2
Order By: Relevance
“…We found that over 25% of workers excreted tt-MA that exceeded the recommended 500 µg/g Cr. Some previous studies have shown that tt-MA levels in different groups of workers who might be exposed to benzene (e.g., refinery workers [23], turnaround maintenance workers [24], traffic policeman [25,26,27] and gasoline station workers [28]) did not exceed 500 µg/g Cr. In one case study conducted in Thailand, it was found that significant differences in tt-MA levels only existed between workers occupationally exposed to benzene and the general population [29].…”
Section: Discussionmentioning
confidence: 99%
“…We found that over 25% of workers excreted tt-MA that exceeded the recommended 500 µg/g Cr. Some previous studies have shown that tt-MA levels in different groups of workers who might be exposed to benzene (e.g., refinery workers [23], turnaround maintenance workers [24], traffic policeman [25,26,27] and gasoline station workers [28]) did not exceed 500 µg/g Cr. In one case study conducted in Thailand, it was found that significant differences in tt-MA levels only existed between workers occupationally exposed to benzene and the general population [29].…”
Section: Discussionmentioning
confidence: 99%
“…About 2% of the total benzene taken up by humans is excreted via urine as tt-MA, and its excretion half-life is < 6 h [ 33 ]. Although urinary tt-MA has been recommended as a biomarker to assess occupational exposure to benzene, Jalai et al showed that tt-MA cannot be used as a reliable biomarker for exposure to low dose benzene [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The levels of tt MA encountered in the urine samples of the workers from Group I and Group II were below the baseline levels reported in the literature, which vary from <0.01 to 0.66 mg g −1 Cr [61,62]. Recent studies have investigated the association between urine tt MA concentrations and occupational/environmental exposure to benzene, suggesting that tt MA is not sensitive enough as a biomarker for monitoring exposure to benzene at concentrations below 0.1 ppm, which is the situation of the study population here [60,63,64]. Melikian et al [65] did an extensive study of the specificity and sensitivity of the biomarkers of benzene, tt MA and S -PMA, at low exposure levels and found that the variation in the percentage of benzene transformed into S -PMA and tt MA diminished as the concentration of benzene itself diminished, especially the conversion of benzene into tt MA.…”
Section: Discussionmentioning
confidence: 77%